Synergistic effect on thermal behavior during co-pyrolysis of lignocellulosic biomass model components blend with bituminous coal - Wu, Zhiqiang; Wang, Shuzhong; Zhao, Jun; Chen, Lin; Meng, Haiyu (Bioresource technology, 2014)
•Co-pyrolysis behavior of lignocellulosic biomass components and bituminous coal was explored.•Positive and/or negative synergistic effects were observed during co-pyrolysis of the mixtures.•Kinetic parameter was solved via using model-free method (Kissinger–Akahira–Sunose).•Nonadditivity performance on the activation energy values of the mixtures was observed. Co-thermochemical conversion of lignocellulosic biomass and coal has been investigated as an effective way to reduce the carbon footprint. Successful evaluating on thermal behavior of the co-pyrolysis is prerequisite for predicting performance and optimizing efficiency of this process. In this paper, pyrolysis and kinetics characteristics of three kinds of lignocellulosic biomass model components (cellulose, hemicellulose, and lignin) blended with a kind of Chinese bituminous coal were explored by thermogravimetric analyzer and Kissinger–Akahira–Sunose method. The results indicated that the addition of model compounds had different synergistic effects on thermal behavior of the bituminous coal. The cellulose showed positive synergistic effects on the thermal decomposition of the coal bituminous coal with lower char yield than calculated value. For hemicellulose and lignin, whether positive or negative synergistic was related to the mixed ratio and temperature range. The distribution of the average activation energy values for the mixtures showed nonadditivity performance.